Battling to the end : conversations with Benoît Chantre - Girard, René, 1923-2015 (Studies in violence, mimesis, and culture., 2010)
In Battling to the End René Girard engages Carl von Clausewitz (1780-1831), the Prussian military theoretician who wrote On War. Clausewitz, who has been critiqued by military strategists, political scientists, and philosophers, famously postulated that ""War is the continuation of politics by other means."" He also seemed to believe that governments could constrain war. Clausewitz, a firsthand witness to the Napoleonic Wars, understood the nature of modern warfare. Far from controlling violence, politics follows in war''s wake: the means of war have become its ends. René Girard